Pacing leads in transcatheter tricuspid valve. (24th May 2021) - Santos, H; Santos, M; Miranda, H; Almeida, I; Paula, S; Figueiredo, M; Neto, M; Sa, C; Chin, J; Almeida, S; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Transcatheter therapy of bioprothesis in tricuspid position and the native tricuspid valve are a growing field in interventional cardiology. Yet, the presence of pacing leads can demand a different approach. We performed a systemic review of this topic to understand the risks and the potential impact on the pacing leads. Objective: Review the evidence regarding the efficacy and safety of pacing leads with the transcatheter tricuspid valve implantation. Methods: A systemic research on MEDLINE and PUBMED with two the following terms "transvenous pacing", "transcatheter valve", "transcatheter tricuspid", "transvalvular leads", "tricuspid valve-in-valve" and "transvalvular pacemaker". 120 results were identified. However, just 5 papers were selected since are the only ones that described the implantation of a transcatheter tricuspid valve in patients with pacing leads and had some follow up, yet one of the papers lacks data and was excluded. The majority of papers reported the success of the procedure yet without a follow-up or the potentials complications on the pacing leads. Results: Four studies were selected, including a total of 33 patients. The studies were performed with different techniques and procedures, as well as the reports regarding the echocardiogram and pacing data before the procedure and during the follow-up. Mean age 59.51 years old, 78.78% were female, 72.72% had NYHA class ≥ III, 21.21% was hospitalized in the previous 6 months, 21.21% had acute or chronic renal insufficiency, 18.18% had cirrhosis or liver disease, 51.52% had other prosthetic valves and 12.12 had history of endocarditis. Acquired etiology for tricuspid valve disease in 63.64%, atrial fibrillation in 60.60%, 78.79% had a tricuspid bioprosthetic valve, one patient had a catheter valve and the rest had a ring with or without homograft valve. 60.60% had moderate or severe tricuspid regurgitation and 15.15% had mixed tricuspid regurgitation and stenosis, with a mean tricuspid valve gradient of 7.22 mmHg. SAPIEN transcatheter valve was used in 78.79% and Melody valve in the rest. The transcatheter tricuspid implantation was a success in 32 patients, without any interference in the pacing leads. Of them, the follow-up period was diverse and heterogeneous with a mean of 13.51 months, a mean tricuspid valve gradient of 5.00 mmHg, and a register of 3 death without any relationship with the transcatheter valve or pacing complications. Was reported three complications during the follow-up regarding the pacing leads, two patients had a marked increase in the right ventricle leads impedance and stimulation threshold and one patient developed a right ventricle lead fracture. Conclusions: 9.28% of the patients submitted to transcatheter tricuspid valve had pacing lead complications. Considering the small sample, further investigation regarding the impact of this procedure in the pacing leads is required for a clear assessment.